Physicochemical and Functional Characteristics of Beverage Sugar Apple Powdered on Level Concentration Different of CMC - Syahraeni Kadir; Abdul Rahim; Rostiati Dg. Rahmatu; Sukisman Sukisman (AGROLAND The Agricultural Sciences Journal (e-Journal), 2015)
The intermediate products of sugar apple do not have an entrepreneurial aspects though they have a longer shelf life than the fresh fruit form unless it processed into the final products of beverages or foods. Therefore it need to continue the processing of sugar apple intermediate products. Some products of them which have a clear prospect entrepreneur among others as both of beverages and functional foods. The Short-term goal of this research is to process the intermediate product into a beverage sugar apple powdered among others. Subsequently the long-term goal of this research is to find ways of processing the intermediate products into final ones that have nutritional value and adequate antioxidants. The results showed that the use of CMC 0.5% gives a better physicochemical and functional characteristics on powdered product of sugar apple. Making the beverage product by filtering the pulp giving better quality of both physicochemical and functional characteristics than without filtering the fleshy part.